Pleistocene biogeochemical record in the SW Pacific Ocean (Images Site MD97-2114, Chatham Rise) - COBIANCHI, MIRIAM; LUPI, CLAUDIA; MANCIN, NICOLETTA; TRATTENERO, IACOPO; BORDIGA, MANUELA; Luciani Valeria; Lirer Fabrizio; Pelosi Nicola; Hall Ian; Sprovieri Mario (Journal of Quaternary Science, 2012)
Through a multidisciplinary approach based on novel micropaleontological and geochemical analyses, the main paleoceanographic and paleoclimate changes that have influenced the surface- and deep-water circulation in the SW Pacific Ocean (Chatham Rise, eastern New Zealand) during the last million years are reconstructed. This region represents a key area for investigating the climate evolution during the Pleistocene because here the largely wind-driven Antarctic Circumpolar Current interacts with the west Pacific Ocean circulation via the Deep Western Boundary Current, the major source of deep water for the whole Pacific Ocean. To understand coupling or decoupling events between sea surface and bottom waters, a continuous marine sedimentary succession since 1.1 Ma, recovered by the IMAGES (International Marine Past Global Change Study) cruise in the SW Pacific Ocean (Core MD97-2114), has been investigated based on calcareous planktonic and benthic microfossil content and C and O isotope record performed on planktonic and benthic foraminiferal tests. Results show the occurrence of long- and short-term patterns of climate and ocean circulation in the last million years as the result of the interplay of ice-sheet dynamics, surface tropical versus polar water inflow, and trophic status of the surface water.